PROBLEMATIKA PERNIKAHAN DINI DI DESA LARANGAN PERRENG KECAMATAN PRAGAAN KABUPATEN SUMENEP - Moh Thayyib (Fakultas Dakwah Institut Dirosat Islamiyah Al-Amien Prenduan, 2020)
The Abstract Every stages of individuals faced with a crisis which is a task of the development of the unique to be solved. The crisis is not a catastrophe but a turning point marked by the increased vulnerability and the potential of the person, the more individuals successfully resolve the crisis that it faces, the more healthy development of the individual. In developing countries marriage often is used as a sign for a for otherwise enter adulthood.” While the fact individuals who undergo early marriage instead there is no sign of maturity at all. It happened in our village Ban Perreng where children who are still of an early age who are married often do not signify what has been stated by Arnett in the book John W. Santrokch titled “Life-Span Development”. Keywords: Problems, Early Marriage.